Literature Review Artikel: Potensi Mitragyna speciosa (Kratom) sebagai Aktivitas Antioksidan, Antidiabetes, Antiinflamasi, dan Antimikroba - Ramadhan, Farhan (STIKes Ibnu Sina Ajibarang, 2025)
Mitragyna speciosa, or kratom, has attracted attention as a potential therapeutic agent in the treatment of various health conditions. This study aimed to evaluate the antioxidant, antidiabetic, anti-inflammatory, and antimicrobial activities of kratom leaf extract. The results showed that kratom extract had high total phenolics, with IC50 values ​​for DPPH and ABTS antioxidant activities of 21.61 µg/mL and 9.33 µg/mL, respectively. In the context of antidiabetic, kratom extract significantly reduced blood glucose levels in a diabetic rat model, and showed positive effects in an oral glucose tolerance test. Anti-inflammatory activity was evaluated through the reduction of pain and inflammation in the animal model, while antimicrobial activity was demonstrated by the inhibition of the growth of pathogenic bacteria, including Salmonella typhi and Bacillus subtilis, with MICs of 6.25 mg/mL and 3.12 mg/mL, respectively. These findings support the potential of Mitragyna speciosa as a multifunctional therapeutic agent, although further studies are needed to understand its mechanisms and applications in clinical treatment.